The Relationship Between Self-Checkout Quality and Customer Satisfaction at AEON Malaysia - Lau, Yong He; Zulkipli, Hafizah (Research in Management of Technology and Business, 2025)
The emergence of self-service technologies (SSTs), especially self-checkout systems, has caused a major shift in the retail sector. These technologies are increasingly essential for improving consumer experiences and operational effectiveness. This study aims to study the relationship between consumer satisfaction and the quality of the self-checkout systems at Aeon Seremban 2, Negeri Sembilan, Malaysia. Understanding the variables that affect customers' satisfaction with self-checkout systems is essential given the variety of customers the store services. Using a simple random sampling method, 384 respondents were selected from approximately in Seremban, Negeri Sembilan. This study takes a quantitative approach, collecting primary data using questionnaires that are analysed with SPSS software. The findings reveal a positive relationship between ease of use, convenience, and reliability with customer satisfaction among customers at Aeon Seremban 2. These results underscore the importance of user-friendly and efficient self-checkout systems in enhancing customer experiences. Grounded in the Technology Acceptance Model (TAM), the study highlights how user-friendly and efficient self-checkout systems enhance satisfaction levels, offering actionable insights for retailers. Although limited to a single location, this research provides valuable implications for optimizing self-checkout technologies to improve customer satisfaction and loyalty.